Maybe a free thinker but not a critical one: High conspiracy belief is associated with low critical thinking ability - Lantian, Anthony; Bagneux, Virginie; Delouvée, Sylvain; Gauvrit, Nicolas (Applied cognitive psychology, 2021)
Critical thinking is of paramount importance in our society. People regularly assume that critical thinking is a way to reduce conspiracy belief, although the relationship between critical thinking and conspiracy belief has never been tested. We conducted two studies (Study 1, N = 86; Study 2, N = 252), in which we found that critical thinking ability—measured by an open‐ended test emphasizing several areas of critical thinking ability in the context of argumentation—is negatively associated with belief in conspiracy theories. Additionally, we did not find a significant relationship between self‐reported (subjective) critical thinking ability and conspiracy belief. Our results support the idea that conspiracy believers have less developed critical thinking ability and stimulate discussion about the possibility of reducing conspiracy beliefs via the development of critical thinking.